2014
DOI: 10.1007/s12264-014-1479-3
|View full text |Cite
|
Sign up to set email alerts
|

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats

Abstract: Amyloid β-peptide (Aβ) has been implicated as a key molecule in the neurodegenerative cascades of Alzheimer's disease (AD). Humanin (HN) is a secretory peptide that inhibits the neurotoxicity of Aβ. However, the mechanism(s) by which HN exerts its neuroprotection against Aβ-induced ADlike pathological changes and memory deficits are yet to be completely defined. In the present study, we provided evidence that treatment of rats with HN increases the number of dendritic branches and the density of dendritic spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…It has been reported that HN increases the ATP levels in serum-deprived human lymphocytes, TE671 muscle cells, and SKN-MC neural cells [21]. It also inhibits apoptosis and reduces the oxidative stress induced by Ab 1-42 [22]. The highly selective effect of HN on cell death associated with AD indicates that it could be promising for AD therapy [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HN increases the ATP levels in serum-deprived human lymphocytes, TE671 muscle cells, and SKN-MC neural cells [21]. It also inhibits apoptosis and reduces the oxidative stress induced by Ab 1-42 [22]. The highly selective effect of HN on cell death associated with AD indicates that it could be promising for AD therapy [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…HN has been shown to be neuroprotective in several models of adult neurologic disease. It is most extensively studied in murine models of Alzheimer's disease, where exogenous administration has been shown to inhibit Aβ neurotoxicity and improve functional outcomes (Chai et al, ). Similar findings have been seen with adult models of stroke and amyotrophic lateral sclerosis (Matsuoka, Hashimoto, Aiso, & Nishimoto, ; Xu, Chua, Gao, Hamdy, & Chua, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is validated by the precipitous drop in the levels of plasma ascorbate (a powerful antioxidant) over the same timeframe [206]. Humanin has been shown to be a key modulator of oxidative stress via the induction of antioxidant enzymes such as SOD [227,231,254] and glutathione peroxidase [226] as well as mediating chaperone-mediated autophagy [230], suggesting a comparable action for s-humanin. Additionally, studies have shown that oxidative stress is widely involved in the development of various neuropathologies that can be counteracted by the effects of humanin.…”
Section: Tissue Regulationmentioning
confidence: 92%
“…Additionally, it has been shown that hibernating ground squirrels do not appear to show any significant neurodegeneration upon exiting from a torpor bout, making the squirrel an excellent model to contribute to the study of neurological disorders such as Alzheimer's [15]. As previously mentioned, the neurons in squirrel brain retract and reduce in size and thereby causing its activation [226]. Therefore, increases in both s-humanin transcript and protein levels in the cortex are highly indicative of its protective function for areas of highlevel cognition and survival.…”
Section: Tissue Regulationmentioning
confidence: 98%
See 1 more Smart Citation